Longitudinal Macular Structure-Function Relationships in Glaucoma and Their Sources of Variability - Nouri-Mahdavi, Kouros; Fatehi, Nima; Caprioli, Joseph (American journal of ophthalmology, 2019)
To review central structure-function (SF) relationships in glaucoma; to compare contributions of within-session and between-session variability to total variability of macular optical coherence tomography (OCT) thickness measurements; and to test the hypothesis that longitudinal within-eye variability of central SF relationships is smaller than between-individual variability. We reviewed the pertinent literature on central SF relationships in glaucoma. Thirty-eight eyes (20 normal or glaucoma subjects) had ×3 macular images per session over 3 sessions, and superpixels thickness measurements for ganglion cell layer (GCL), ganglion cell/inner plexiform layer (GCIPL), ganglion cell complex (GCC), and full macular thickness (FMT) were exported. Linear mixed models were used for estimating contributions of between- and within-session variability to total thickness variability. One hundred twenty eyes with ≥3 10° visual fields (VFs)/OCT images were enrolled for the longitudinal study. We investigated within-eye longitudinal SF relationships (GCIPL thickness vs VF total deviations) with a change-point regression model and compared within-eye to between-individual variabilities with components-of-variance models. In the cross-sectional study, the between-session component contributed 8%, 11%, 11%, and 36% of total variability for GCL, GCIPL, GCC, and FMT, respectively. In the longitudinal study, between-individual variability explained 78%, 77%, and 67% of total SF variability at 3.4°, 5.6°, and 6.8° eccentricities, respectively (P < .05). SF relationships remained stable over time within individual eyes. Within-session variability accounts for most of macular thickness variability over time. Longitudinal within-eye SF variability is smaller than between-individual variability. Study of within-eye SF relationships could help clinicians better understand SF linking in glaucoma and help refine progression algorithms. NOTE: Publication of this article is sponsored by the American Ophthalmological Society.